Analisis Partisipasi Siswa dalam Pembelajaran Agama Islam: Analisis Studi Literatur - Nofmiyati Nofmiyati; Miftahuddin Miftahuddin; M. Fahli Zatrahadi (Fakultas Tarbiyah dan Keguruan, 2023)
This study aims to identify the factors that influence student participation and the obstacles they face. This research method uses a literature review approach by conducting a literature review of the literature related to student participation in Islamic religious learning. The research results show that learning methods that involve students actively can increase student participation. However, there are obstacles such as lack of time, limited space, lack of student knowledge, lack of student-teacher interaction, and a lack of varied learning resources. In overcoming these barriers, it is important to implement effective learning methods, provide adequate learning resources, involve parents, and create a supportive environment. Thus, student participation in learning Islamic religion in schools can be increased for the formation of strong characters.